Strategi Komunikasi Pemasaran Afiliator dalam Menarik Minat Belanja Konsumen Pada Sebuah Produk di Marketplace - Dewa Ayu, Dewa Ayu Mirna Wati; Suniantara, I Ketut Putu; Sastrawan, I Nengah Oka (UHN IGB Sugriwa Denpasar, 2024)
Social media is a digital platform that facilitates its users to facilitate interactive social interactions. Social media is also an effective way to market products and services widely which can increase sales and advance business. In an effort to attract visitors to open and even shop on an e-commerce platform, of course it cannot be separated from the many people who influence (poison) promotions with advertisements on various social media so that many people are interested in visiting the e-commerce and even to buy the products they sell. In order to convey information and other interests, a person or group of people who are considered influential are needed to guide opinions and voice marketing interests such as promotions. Currently, many new professions have emerged, as a result of the high number of social media users in Indonesia, one of which is content creator. A content creator is someone who focuses on creating content, whether in the form of writing, images, videos, podcasts, or other forms. Currently, many content creators have joined affiliates to earn commissions. Affiliates will get a commission based on their performance in promoting Shopee products and sharing affiliate links. Therefore, this research is very interesting to research because it is to find out what kind of strategies are used by Shopee affiliates in promoting products. The research method used is a qualitative descriptive method with the aim of understanding the marketing communication strategies used by Shopee affiliates and what the results of the strategies that have been implemented are